Power of the Circumplex: Incremental validity of intersection traits in predicting counterproductive work behaviors. (12th August 2013) - Gonzalez‐Mulé, Erik; DeGeest, David; Mount, Michael K.
<x xml:space="preserve">Abstract</x> This study examines the role of the circumplex model of personality in predicting counterproductive work behaviors (CWBs). Drawing on the fidelity‐bandwidth principle, we investigate the hypotheses that each of the three sets of circumplex traits representing the intersections of conscientiousness–agreeableness, conscientiousness–emotional stability, and agreeableness–emotional stability will account for significant incremental variance over five‐factor model (FFM) traits in predicting CWBs. Results indicated the circumplex traits contribute incremental variance over the FFM traits, are relatively more important than the FFM traits, and account for 1.5–2.0 times more variance in the total R2 associated with CWBs. Collectively, these findings show that circumplex traits capture unique information not explained by FFM traits, and this information leads to a better understanding of the dispositional nature of CWBs.